Pemberdayaan Masyarakat dalam Pemahaman Tentang Akad Kafalah Berdasarkan Kompilasi Hukum Ekonomi Syariah (KHES) di Desa Pandau Jaya Kecamatan Siak Hulu - Muhammad Azani; Hasan Basri (Wisanggeni : Jurnal Pengabdian Masyarakat, 2021)
The results of community service in the form of legal counseling in Pandau Jaya Village, Siak Hulu District are as follows: Has increased participants' understanding of the Kafalah contract in the Sharia Economic Law Compilation (KHES). The material presented includes the pillars of the kafalah contract, the terms for the object of the kafalah contract, the types of the kafalah contract, the implementation of the kafalah contract, and the parties who die in the kafalah contract. After delivering the material, participants were asked a number of questions related to the material presented. The distribution of participants' answers after legal counseling can be stated that participants understand the material presented. In general, participants can understand the kafalah contract in KHES. There were 6 (six) questions given, question number 3 about the type of kafalah contract and number 5 about the guarantor who passed away received the highest answers with 84% and 85%. Problems that arise in the form of participant questions are questions about the difference between the kafalah contract and the rahn contract as a guarantee contract and questions about the pillars of the kafalah contract. Kafalah is the equivalent of dhamman, which means guarantee, but in its development, Kafalah is identical to kafalah al-wajhi (personal guarantee, self-guarantee), while dhamman is identical to collateral in the form of goods / assets. This concept is different from akad rahn which means collateral, but collateral from the person in debt. In addition, questions about the pillars of the kafalah contract, the answer refers to Article 22 KHES 335 which states that the pillars of the kafalah contract are the guarantor (Kafil), the guaranteed party (Makful 'Anhu), the indebted party (Makful Lahu), the object (Makful Bihi), and Akad. The kafalah contract in sharia banking activities is used as a form of bank service to guarantee activities or businesses proposed by customers. Guarantee in the form of kafalah can be carried out with the model of asset guarantee (kafalah bi al-mal) and person / institution guarantee (kafalah bi al-nafs). Financially or institutionally, the bank guarantees the party applying for guarantee services.